The continuous rise - during economic growth, the COVID-19 Pandemic, and conflict - in the adoption of labor-saving agricultural technologies in Myanmar: Evidence and implications - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
After decades of isolationism and economic stagnation, Myanmar opened its economy in the beginning of the 2010s, leading to rapid economic growth (Myanmar’s Gross Domestic Product (GDP) was almost 50 percent larger in 2020 than in 2011). But the COVID-19 health crisis that started in 2020 and a military coup in the beginning of 2021 – and the subsequent increase in conflicts, forced displacements, and migration – dramatically reversed that outlook, with Myanmar’s GDP in 2022 estimated to be 13 percent smaller than three years earlier. The agricultural sector also changed accordingly during this period.